Diagnostic potential of total serum ghrelin in autoimmune gastritis: A systematic review and meta-analysis - Iqbal Taufiqqurrachman; Andro Pramana Witarto; Ari Fahrial Syam; Murdani Abdullah; Sigit Ari Saputro; Irine Normalina; Muhammad Miftahussurur; Yoshio Yamaoka (PLoS ONE, 2026)
Background Autoimmune gastritis (AIG) is a chronic inflammatory condition characterized by the destruction of gastric parietal cells. The invasive nature of diagnostic procedures and risk of confounding factors hinder the development of reliable diagnostic tools for AIG. Methods We conducted a systematic search of four databases. After assessing the study quality using the ROBINS-E tool, a meta-analysis was performed using a random-effects model. Meta-regression and sensitivity analyses were conducted to explore the sources of heterogeneity and impact of study bias, Results The pooled mean difference in total serum ghrelin (pmol/L) between patients with AIG and healthy controls was −65.28 (95% CI: −178.54, 47.97). Subgroup analysis showed that the mean differences in serum ghrelin for mild, moderate, and severe atrophy were −78.85 (95% CI: −165.17, to 7.48), −91.97 (95% CI: −183.11, to −0.84), and −110.67 (95% CI: −204.77, to −16.56), respectively. The sensitivity analysis confirmed that the exclusion of studies with high-risk bias did not significantly alter the results. Meta-regression indicated that BMI contributed substantially to heterogeneity. Conclusions Although total serum ghrelin levels were not significantly different between patients with AIG and healthy controls, significantly lower levels were observed in patients with moderate-to-severe gastric atrophy. Given the high heterogeneity and limitations of existing studies, the diagnostic utility of serum ghrelin in AIG warrants further investigation.